Multidimensional approach to peri-urban land system, in the southern region of Santa Fe. - ARADAS DÍAZ, M. E. (Universidad Nacional del Litoral, 2020)
Peri-urban land system is affected by multiple dimensions and actors that make its management complex. In the Territorial Innovation Platform of the INTA in Oliveros, the following dimensions have been identifi ed: economic/productive, geographical, ecological and environmental, organiztional-political, socio-cultural, technological and institutional. The aim of this paper is to deepen the concept and multidimensional management of the peri-urban soil, linking them to the institutional objectives. Methodologically, a description of each one of them is made, making a diagram that allows to visualize the interrelations between them. The results of the interaction between the dimensions make is possible to link concepts such as productive diversity, critical space, territory in dispute, diversity of quality and types of soil, governance defi ciencies, heterogeneity in the size and methods of land use, land tenure, laws and regulations and diversity of actors involved, among others, imply a multidimensional approach, which, in turn, is linked to institutional objectives: competitiveness, equity and environmental health. The systemic approach facilitates the understanding and dimensioning of the peri-urban land as a living space where its properties emerge from the interactions between the dimensions that compose it.